EFEKTIVITAS PENERAPAN MODEL PROJECT BASED LEARNING TERHADAP MOTIVASI DAN KEMAMPUAN PEMAHAMAN KONSEP SISWA SEKOLAH MENENGAH KEJURUAN - Nugrah Wulandari AL; Riana T. Mangesa; Anas Arfandi; Supriadi; Abdul Muis Mappalotteng (UNM Journal of Technology and Vocational, 2023)
This study aims to examine (a) the increase of students' learning motivation after applying the Project Based Learning model in the Basic Programming Subject at SMKN (public vocational high school) 2 Gowa, (b) the increase of students' conceptual understanding skills after applying the Project Based Learning Model in Basic Programming Subject at SMKN 2 Gowa, (c) whether the students' learning motivation in applying the Project Based Learning model is more effective than students' motivation in applying conventional learning model, and (d) whether the students' conceptual understanding skills in applying Project Based Learning model are more effective than the students’ conceptual understanding skills in applying conventional learning model in Basic Programming Subject at SMKN Negeri 2 Gowa. The type of research used is experimental research. The experimental design used is the Nonequivalent Control Group Design in the form of PretestPosttest Design with a sample of 68 students. Data collecting employed questionnaire and test of conceptual understanding skills. The collected data were analyzed using descriptive statistical analysis and inferential statistical analysis. The results of the study are reveal that (a) there is an increase in students' learning motivation after applying the Project Based Learning model in Basic Programming Subject at SMKN Negeri 2 Gowa, (b) there is an increase in students' conceptual understanding skills after applying the Project Based Learning model in Basic Programming Subject at SMKN 2 Gowa, (c) the students’ learning motivation in applying the Project Based Learning model is more effective than students’ learning motivation in applying conventional learning model in Basic Programming Subject at SMKN 2 Gowa, and (d) the students' conceptual understanding skills in applying Project Based Learning model is more effective than the students' conceptual understanding skills in the applying conventional learning model in Basic Programming Subject at SMKN 2 Gowa. Based on the aforementioned results, it can be concluded that the application of the Project Based Learning model is effective and can increase students' motivation and conceptual understanding skills in Basic Programming subject at SMKN 2 Gowa.